Aplikasi Door Access dan Motion Sense pada Smart Home menggunakan Microcontroller berbasis Android - Kevin Trisnajaya; Resmana Lim; Leo Willyanto Santoso (Jurnal Infra, 2018)
Smart Home is an application system that is a combination of technology and services that specialize in the home environment with specific functions aimed at improving the efficiency, comfort and security of the occupants. This intelligent home system uses a microcontroller to process functions that Smart Home applications will provide, such functions as rfid for door access and pir sensors for motion detection.To interact with sensors, microcontroller, or other tools through the Internet used Android devices. By using Android users can control the sensors already listed on the Android app with the internet. Android uses JAVA for programming language. Then here the sensor also needs to connect with microcontroller. Microcontroller used is Arduino IDE with WEMOS D1R2 board. Setting the sensor can only be done with a microcontroller, then it's all connected via the internet in order to be applied on Android.The end result of this research is the successful communication between the components of the device, sensors, and Android devices. Users can open or close the solenoid, users can also turn off or turn on electronic devices using Android.